Collection of Franciscan Monastery : Fraction of Yugoslavian Culture - FRA-YU-KULT. (Siroki Brijeg : Muzej Siroki Brijeg, 1990)
Delimar, Vlasta ; Gorenec, Bojan ; Hadzifejzovic, Jusuf ; Irwin ; Jadran ; Kipke, Zeljko ; Knifer, Julije ; Kovacs, Adrian ; Kozaric, Ivan ; Martk, Vlado ; Petercol, Goran ; Stilinovic, Mladen ; Soskic, Ilija ; Todosijevic, Rasa ; Ves Slikar Svoj Dolg
boek
Keywords: Joegoslavië